1996
DOI: 10.1007/bf00180730
|View full text |Cite
|
Sign up to set email alerts
|

Improving argumentative writing skills: Effect of two types of aids

Abstract: Young children have difficulties writing argumentative texts which contain well-linked arguments and counterarguments even though they are capable of arguing by oral. Two main explanations have been provided to account for those difficulties: a) The writer has to manage alone two different points of view, whereas each of the two (or more) speakers can take charge of one of the points of view. b) The inability of young children to attribute an argumentative valence to statements.In order to improve the ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
8

Year Published

2001
2001
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 18 publications
1
6
0
8
Order By: Relevance
“…As regards the conceptual/linguistic relationship, recent studies have shown that an initial conceptual prewriting session could improve the text quality (Andriessen, Coirier, Roos, Passerault, & Bert-Erboul, 1996;Gombert & Roussey, 1994;Isnard & Piolat, 1994;Kellogg, 1990;Roussey & Gombert, 1996), but this effect is mainly observed in expert writers (Dellerman, Coirier, & Marchand, 1996). Conversely, no research has shown that expert linguists were better at conceptualizing, which, of course, does not mean they are not better at expressing a conceptualization.…”
mentioning
confidence: 99%
“…As regards the conceptual/linguistic relationship, recent studies have shown that an initial conceptual prewriting session could improve the text quality (Andriessen, Coirier, Roos, Passerault, & Bert-Erboul, 1996;Gombert & Roussey, 1994;Isnard & Piolat, 1994;Kellogg, 1990;Roussey & Gombert, 1996), but this effect is mainly observed in expert writers (Dellerman, Coirier, & Marchand, 1996). Conversely, no research has shown that expert linguists were better at conceptualizing, which, of course, does not mean they are not better at expressing a conceptualization.…”
mentioning
confidence: 99%
“…We share the view that argumentation can, on the one hand, be taught to young pupils (Brassart, 1985, Dolz & Pasquier, 1994, Dolz, 1996, Golder, 1996, Garate & Melero, 2000 and, on the other, that children are receptive to this type of instruction, in particular as of the age of 10 years (Gombert & Roussey, 1993, Roussey, Akiguet, Gombert, Piolat, 1995, Roussey & Gombert, 1996, Gombert, 1997). We have already tested the ability of sequential mechanisms, consisting of progressive oral workshops, to improve writing (Auriac-Peyronnet, 1998, 1999.…”
Section: Theoretical Frameworkmentioning
confidence: 65%
“…At the same time, it is a fact that argumentative discourse is primarily an oral behaviour to which children adapt (Francois, 1980;Golder, 1993). Children detect, for example, the valence of argumentative sentences (Brassart, 1985;Roussey & Gombert, 1996). In contrast, subjects aged 10 to 11 years cannot be considered as having a high level of competency (a high level is achieved at about age 17, see Golder, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…It seems that several cognitive, textual and linguistic competencies interact and many factors could affect the planning and control processes during on-line production (see Esperet, 1989;Esperet & Piolat, 1989). Also, if the reservations expressed by authors like Brassart (see Roussey & Gombert, 1996) or Golder (1996) concerning the existence of a prototypical textual schema are admitted, new qualitative research into the description of individual strategies of argumentative writing in young children must be conducted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation